Omega-3 index of erythrocytes and predictors of sudden cardiac death in patients with coronary heart disease and ventricular arrhythmias - E. M. Gavva; D. A. Tsaregorodtsev; I. S. Mamedov; V. A. Sulimov (Кардиоваскулярная терапия и профилактика)
Aim. To assess the association between ω-3 index of erythrocytes and demographic, electrophysiological, and echocardiographic (EchoCG) predictors of sudden cardiac death (SCD) in patients with coronary heart disease (CHD) and ventricular arrhythmias (VA). Material and methods. The study included 25 patients with a verified diagnosis of CHD and VA. Gas chromatography method was used to measure the content (%) of eicosapentaenoic (EPA) and docosahexaenoic (DHA) polyunsaturated fatty acids (PUFA) in peripheral blood erythrocytes, with the calculation of a summary (EPA + DHA) ω-3 index. All participants underwent 24-hour electrocardiography (ECG) monitoring, with the assessment of maximal, minimal, and mean heart rate (HR), heart rate variability (HRV) parameters (SDNN and pNN50), heart rate turbulence (TO and TS), microvolt T wave alternans (mTWA), and the number of ventricular extrasystoles (VE) and transient and persistent ventricular tachycardia (VT) episodes. All patients also underwent EchoCG. Results. In examined patients, the values of ω-3 index of erythrocytes varied from 1,12% to 6,4% (mean 3,74%, 95% CI 2,02-4,38%). There was a weak correlation between ω-3 index or EPA levels (%) and the HRV parameter of pNN50. In addition, ω-3 index or DHA levels (%) negatively correlated with the daily VE number. The 5:00 AM value of mTWA (II lead, update factor 1/8) weakly correlated withω-3 index and DHA levels. There was a moderate positive correlation between E/A ratio and omega-3 index, or EPA and DHA levels. Conclusion. Patients with CHD and VA were characterised by low ω-3 index values and high (56%) or moderate (44%) levels of cardiovascular risk. The values of ω-3 index positively correlated with the daily VE number and negatively correlated with E/A ratio and pNN50 parameter of HRV.